2019
DOI: 10.3390/ijerph16162982
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Location-Routing Problem in Emergency Logistics Considering Carbon Emissions

Abstract: In order to solve the optimization problem of emergency logistics system, this paper provides an environmental protection point of view and combines with the overall optimization idea of emergency logistics system, where a fuzzy low-carbon open location-routing problem (FLCOLRP) model in emergency logistics is constructed with the multi-objective function, which includes the minimum delivery time, total costs and carbon emissions. Taking into account the uncertainty of the needs of the disaster area, this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…This paper randomly selects 8 cases from the database including small-scale study (Pro1, Pro2, Pro3, Pro4), medium-scale study (Pro5, Pro6, Pro7) and large-scale study (Pro8), the detailed information is shown in Table 5. Parameters of vehicles are shown in Table 6 according to references [21,50,51] and parameters of the proposed algorithm are shown in Table 7 according to references [10,[52][53][54].…”
Section: Test Casesmentioning
confidence: 99%
“…This paper randomly selects 8 cases from the database including small-scale study (Pro1, Pro2, Pro3, Pro4), medium-scale study (Pro5, Pro6, Pro7) and large-scale study (Pro8), the detailed information is shown in Table 5. Parameters of vehicles are shown in Table 6 according to references [21,50,51] and parameters of the proposed algorithm are shown in Table 7 according to references [10,[52][53][54].…”
Section: Test Casesmentioning
confidence: 99%
“…The carbon emissions of transportation are proportional to fuel consumption. This paper refers to the literature [42] to calculate the amount of carbon dioxide from fuel consumption. Therefore, the carbon emissions E co 2 and its costs C 3 of the CVRP model can be expressed as Equations (4) and (5).…”
Section: Parameters and Variablesmentioning
confidence: 99%
“…If a facility is assigned excessive collection trips, the given limit is decreased. Table 10 presents the upper limits for all 6 DFs, where U r represents the given limit for disposal facility r. According to the previous studies [10,11,42,48], the parameters related to the CVRP model are shown in Table 11. The penalty value p is set to half of the fixed costs per unit vehicle.…”
Section: Experimental Designmentioning
confidence: 99%
“…It is obviously better than that of the standard colony algorithm (3840.55). In order to demonstrate the superiority of this method, intelligent algorithm (this work), Multiple Ant Colony Optimization Algorithm (MACOA) [65] and Non-dominated Sorting Genetic Algorithm (NSGA) [66] are selected in this paper to solve the problem respectively. We assumed the number of iterations as 100 times.…”
Section: Effectiveness Analysis Of Iacats Algorithmmentioning
confidence: 99%